Effects of Azospirillum brasilense on growth and yield compounds of maize grown at nitrogen limiting conditions - Garcia,Mayara M. (2017)
This study aimed to evaluate the agronomic performance of different doses of Azospirillum brasilense in peat formulation on maize crop grown under limited N fertilization, using a completely randomized design with four replicates. The treatments tested consisted of absence of N fertilizer, the full N recommendation and a combination of the half of recommended N associated with the inoculation of three doses of A. brasilense in peat formulation (100 g, 150 g or 200 g per 25 kg of seeds). The following variables were evaluated: insertion height of the first ear height, number of kernel per row, number of row per ear, shoot dry biomass, root dry biomass, chlorophyll content, thousand seed weight, grain N content, shoot N content and grain yield. Half the dose of N fertilizer combined with 150 g per 25 kg of seeds of A. brasilense in peat formulation provided significantly superior results in agronomic performance of maize, particularly regarding grain yield, thousand seed weight and dry biomass of both shoot and root